2019
DOI: 10.1111/tpj.14573
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation‐dependent control of an RNA granule‐localized protein that fine‐tunes defence gene expression at a post‐transcriptional level

Abstract: Summary Mitogen‐activated protein kinase (MAPK) cascades are key signalling modules of plant defence responses to pathogen‐associated molecular patterns [PAMPs; e.g. the bacterial peptide flagellin (flg22)]. Tandem zinc finger protein 9 (TZF9) is a RNA‐binding protein that is phosphorylated by two PAMP‐responsive MAPKs, MPK3 and MPK6. We mapped the major phosphosites in TZF9 and showed their importance for controlling in vitro RNA‐binding activity, in vivo flg22‐induced rapid disappearance of TZF9‐labelled pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 61 publications
0
29
0
Order By: Relevance
“…Furthermore, the overexpression of these genes usually can enhance abiotic stress tolerance [ 17 , 23 , 27 , 28 ]. AtTZF9 is the only known RR-TZF gene that regulates immunity in Arabidopsis [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the overexpression of these genes usually can enhance abiotic stress tolerance [ 17 , 23 , 27 , 28 ]. AtTZF9 is the only known RR-TZF gene that regulates immunity in Arabidopsis [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In response to flagellin (flg22) treatment, MPK3/MPK6 phosphorylated another p-body component, tandem zinc finger protein 9 (TZF9), and led to a decrease of TZF9-associated p-bodies in Arabidopsis protoplasts [ 43 ] ( Figure 2 d). A comparison of the transcriptome and translatome between the wild type and tzf9 mutant revealed that TZF9 can regulate flg22-dependent gene expression at the translation level [ 43 ]. Together with data from Yu et al [ 42 ], the treatment of flg22 induced the disassembly of p-bodies in both cases.…”
Section: P-bodiesmentioning
confidence: 99%
“…( c ) Yu et al (2019) demonstrated that the treatment of flg22 triggered the disassembly of DCP1-associated p-bodies and differential mRNA decay in Arabidopsis protoplasts [ 42 ]. ( d ) The treatment of flg22 led to the decrease of TZF9-containing granules and the release of translation repression in Arabidopsis protoplasts [ 43 ]. The spherical dark-shade clusters in the background of the upper panel of (d) are chloroplasts (Ch).…”
Section: Figurementioning
confidence: 99%
“…Several post-transcriptional/translational mechanisms controlling protein abundance have just recently been uncovered in plant immunity (Meteignier et al, 2017;Xu et al, 2017;Tabassum et al, 2019). Therefore we investigated reshaping of the proteome in the steady state shift from growth to pattern triggered immunity (PTI).…”
Section: Introductionmentioning
confidence: 99%